2016
DOI: 10.1136/gutjnl-2015-310904
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte MyD88 affects bile acids, gut microbiota and metabolome contributing to regulate glucose and lipid metabolism

Abstract: ObjectiveTo examine the role of hepatocyte myeloid differentiation primary-response gene 88 (MyD88) on glucose and lipid metabolism.DesignTo study the impact of the innate immune system at the level of the hepatocyte and metabolism, we generated mice harbouring hepatocyte-specific deletion of MyD88. We investigated the impact of the deletion on metabolism by feeding mice with a normal control diet or a high-fat diet for 8 weeks. We evaluated body weight, fat mass gain (using time-domain nuclear magnetic resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(124 citation statements)
references
References 68 publications
7
116
0
1
Order By: Relevance
“…An interesting study showed that transferring microbiota from an obese subject to a lean subject resulted in weight gain (30). The hepatocytes orchestrate the regulatory mechanisms of bile acids, microbiota and metabolome to affect glucose and lipid metabolism (31). Future research may prove the existence of a link between microbiota and beta-cell function.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting study showed that transferring microbiota from an obese subject to a lean subject resulted in weight gain (30). The hepatocytes orchestrate the regulatory mechanisms of bile acids, microbiota and metabolome to affect glucose and lipid metabolism (31). Future research may prove the existence of a link between microbiota and beta-cell function.…”
Section: Discussionmentioning
confidence: 99%
“…Receptor activator of NF-κB, a prototypical activator of NF-κB, regulates hepatic insulin sensitivity 184. Deletion of hepatic MyD88 results in liver inflammation and hepatic insulin resistance also affecting the gut microbiota composition and metabolome 185. Therefore, several studies using hepatocyte-specific targeting of genes have now strongly supported the notion that hepatocytes are major metabolic ‘players’ in the development of metabolic inflammation in and beyond the liver.…”
Section: Putative Mechanisms Linking Nafld To Extrahepatic Conditionsmentioning
confidence: 99%
“…They found that in absence of MyD88 specifically in the hepatocyte, mice were predisposed to glucose intolerance, inflammation, liver fat accumulation and hepatic insulin resistance, and this was independent of body weight and adiposity 50. In addition, this deletion profoundly affected the gut microbiota composition, therefore, showing that host genetics also contribute to shape the microbiota and in turn host metabolism.…”
Section: Non-alcoholic Fatty Liver Disease Metabolic Inflammation Anmentioning
confidence: 99%